Heidegger and French philosophy : humanism, antihumanism, and being - Rockmore, Tom, 1942- (London ; New York : Routledge, 1995)
Martin Heidegger's impact on contemporary thought is important and controversial. However in France, the influence of this German philosopher is such that contemporary French thought cannot be properly understood without reference to Heidegger and his extraordinary influence. Tom Rockmore examines the reception of Heidegger's thought in France. He argues that in the period after the Second World War, due to the peculiar nature of the humanist French Philosophical tradition, Heidegger became the master thinker of French philosophy. Perhaps most importantly, he contends that this reception - first as philosophical anthropology and later as postmetaphysical humanism - is systematically mistaken.
Chapter 1 HEIDEGGER AS A -- chapter 2 HEIDEGGER AND THE MASTER THINKER IN FRENCH PHILOSOPHY -- chapter 3 GERMAN PHENOMENOLOGY, FRENCH PHILOSOPHY, AND SUBJECTIVITY -- chapter 4 HEIDEGGER, SARTRE, AND FRENCH HUMANISM -- chapter 5 JEAN BEAUFRET AND THE -- chapter 6 HEIDEGGER'S -- chapter 7 ON HEIDEGGER AND CONTEMPORARY FRENCH PHILOSOPHY -- chapter 8 HEIDEGGER'S POLITICS AND FRENCH PHILOSOPHY -- chapter 9 HEIDEGGER, FRENCH PHILOSOPHY, AND THE PHILOSOPHICAL TRADITION.
Includes bibliographical references (pages 190-243) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Heidegger, Martin, -- 1889-1976.; Heidegger, Martin, -- 1889-1976; Philosophy, French -- 20th century; Philosophie française -- 20e siècle.; PHILOSOPHY -- History & Surveys -- Modern; Philosophy, French; 1900-1999; Philosophy; France